Diagnosis and management of splenic tuberculosis: a case report and literature review - Liu, Peijun; Liu, Na; Li, Fanghao (Frontiers in Medicine, 2025)
Splenic tuberculosis is a rare form of extrapulmonary tuberculosis, that is often caused by hematogenous dissemination. A 53-year-old female presented with multiple enlarged lymph nodes and a splenic mass identified during a routine health check. Imaging revealed widespread lymphadenopathy and multiple splenic nodules, raising suspicion for lymphoma. The laboratory findings showed an elevated erythrocyte sedimentation rate and mild liver function abnormalities, with no significant tumor markers or inflammatory indicators. Histopathology of lymph node and splenic biopsies revealed granulomas with epithelioid cells and multinucleated giant cells. Acid-fast staining confirmed the presence of Mycobacterium tuberculosis, indicating the presence of splenic tuberculosis. The patient was treated with a standard anti-tuberculosis regimen and adjunctive hepatoprotective therapy, resulting in clinical improvement, and was discharged in stable condition. This case underscores the diagnostic challenges of splenic tuberculosis due to its non-specific presentation and highlights the importance of histopathological evaluation for timely diagnosis and treatment.